A multi-objective life cycle approach for optimal building design: A case study in Finnish context. (1st February 2017) - Pal, Sudip Kumar; Takano, Atsushi; Alanne, Kari; Palonen, Matti; Siren, Kai
Abstract: This study demonstrates the possibility to use energy-cost optimal building designs based on life cycle approach. There is a lack of studies that cover the comprehensive assessment of both embodied energy (EE) and operational energy (OE) in a single optimization problem. The primary goal of the current study is to compare the optimized results of using OE+EE together and OE only. The optimization is performed on a case study building (townhouse) in Finland with three structural alternatives (i.e., reinforced concrete (RC); cross-laminated timber (CLT) and Steel). Different options for insulation thickness of external wall, roof, floor and window types were considered as decision variables as the scope of the present study is on building envelope. The objectives of the optimization are to minimize life cycle energy (LCE) and life cycle costs (LCC). The LCE difference between the most and least energy efficient solution on the pareto front is greater in case of the OE optimization, compared to OE+EE optimization. For all studied structures, the EE of the optimal solutions from OE+EE optimization ranges 16%–23% of LCE. Many of the non-dominated optimal solutions obtained from the OE+EE optimization shows a higher U-value for the building envelope components compared to the optimal solutions from the OE optimization. A relationship between both OE and EE with the overall thermal resistance of the building envelope is discussed to obtain a deeper understanding of such differences in U-value for the optimal solutions obtained from the OE+EE and OE optimization. Highlights: A case study demonstration of life cycle optimization with focus on building envelope. Both embodied energy (EE) and operational energy (OE) is included in optimization. The difference in the optimized results when using OE+EE together and OE only were analyzed. Many of OE+EE optimal solutions are indicated by higher U-value, compared to OE optimization. Among the optimal solutions, the EE share ranges from 16 to 23% of life cycle energy.